A marine connection between parnaíba and paraná basins during the eifelian/givetian transition: Review and new data - Grahn, Yngve; Horodyski, Rodrigo Scalise; Mendlowicz Mauller, Paula; Bosetti, Elvio P.; Ghilardi, Renato P. [UNESP]; Carbonaro, Fabio A. (Sociedade Brasileira de Paleontologia, 2016)
A long-lived marine seaway between the Parnaíba and Paraná basins occurred during a global marine transgression between Brazilian intracratonic basins (except for the Solimões Basin) in the latest Eifelian/earliest Givetian (Middle Devonian). As a result of this transgression a catastrophic event (KAČÁK) in combination with the immigration of warm water Appalachian and Old World faunas contributed to the collapse of the Malvinokaffric Realm in the Paraná Basin. In the Alto Gaŗas and Apucarana sub-basins, the transgression is notable in the early Givetian with an impoverished shelly fauna following the KAČÁK post-extinction event in the earliest Givetian.
Keywords: Early givetian; Malvinokaffric realm; Paraná basin; Parnaíba basin; Seaway; Taphonomic bias